Hubungan Motivasi Pasien Tentang Pencegahan Penularan Dengan Kepatuhan Penggunaan Masker Pada Pasien Tuberkulosis Paru - Ade Ella Nur Rizky Oktaviyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
One of the factors that influence compliance is individual motivation. There are still many pulmonary tuberculosis patients who do not wear masks, this can have an impact on disease transmission. Poor individual motivation can affect someone's compliance. The purpose of this research is to determine the relationship of patient motivation regarding prevention of transmission with adherence to the use of masks in patients with pulmonary tuberculosis in Rambipuji Health Center, Jember Regency. This research uses descriptive correlative type of research. In this study using a cross-sectional approach. The sample of this study was taken using simple random sampling, namely pulmonary tuberculosis patients at the Rambipuji Health Center in Jember Regency, totaling 105 patients but only 50 patients were used as samples. This research was conducted by giving a questionnaire to pulmonary tuberculosis patients to find out the patient's motivation about preventing transmission by adhering to the use of masks. The results of the study were analyzed using the Lambda Correlation Test, the results of the analysis found that the motivation of patients was good motivation (22%), patient motivation was sufficient (56%), and patient motivation was less motivation (22%). Whereas adherence to the use of masks in pulmonary tuberculosis patients is compliant (36%), and non-compliant (64%). The Lambda Correlation Test results obtained from the variable compliance with ρ = 0.389 positive direction with a value of ρ count of 0.027 <0.05 which means there is a relationship between patient motivation about prevention of transmission with compliance with the use of masks in patients with pulmonary tuberculosis in Rambipuji Health Center, Jember District. It is recommended that further studies be able to conduct more in-depth research related to the relationship of patient motivation regarding the prevention of transmission with adherence to the use of masks in pulmonary tuberculosis patients